Alumni series: immersive experience at the 76th World Health Assembly / Md Faizul Kamaruddin - Kamaruddin, Md Faizul (Faculty of Pharmacy, 2023)
The World Health Assembly (WHA) is the supreme decision-making body of the World Health Organization (WHO). Participating in the WHA was an unparalleled experience that provided invaluable insights into global health governance and fostered collaborative efforts towards improving public health worldwide. Being selected to attend the WHA in Geneva, Switzerland, alongside distinguished individuals like The Honourable Health Minister, Dr. Zaliha binti Mustafa, and Director General of Health, Datuk Dr. Muhammad Radzi bin Abu Hassan, was an immense privilege. This opportunity provided an exceptional platform for engaging with representatives from member states, international organisations, and civil society. The assembly was convened with the purpose of discussing and formulating policies on crucial health issues, influencing the WHO's agenda, and adopting resolutions to tackle global health challenges. The diverse array of participants brought together a wide range of expertise, perspectives, and experiences, fostering a dynamic and lively environment conducive to the exchange of knowledge and collaborative efforts.